Measurement of stray radiation within a scanning proton therapy facility: EURADOS WG9 intercomparison exercise of active dosimetry systems. Issue 5 (24th April 2015) - Farah, J.; Mares, V.; Romero‐Expósito, M.; Trinkl, S.; Domingo, C.; Dufek, V.; Klodowska, M.; Kubancak, J.; Knežević, Ž.; Liszka, M.; Majer, M.; Miljanić, S.; et al.
Abstract : Purpose: To characterize stray radiation around the target volume in scanning proton therapy and study the performance of active neutron monitors. Methods: Working Group 9 of the European Radiation Dosimetry Group (EURADOS WG9—Radiation protection in medicine) carried out a large measurement campaign at the Trento Centro di Protonterapia (Trento, Italy) in order to determine the neutron spectra near the patient using two extended‐range Bonner sphere spectrometry (BSS) systems. In addition, the work focused on acknowledging the performance of different commercial active dosimetry systems when measuring neutron ambient dose equivalents, H ∗ (10), at several positions inside (8 positions) and outside (3 positions) the treatment room. Detectors included three TEPCs—tissue equivalent proportional counters (Hawk type from Far West Technology, Inc.) and six rem‐counters (WENDI‐II, LB 6411, RadEye™ NL, a regular and an extended‐range NM2B). Meanwhile, the photon component of stray radiation was deduced from the low‐lineal energy transfer part of TEPC spectra or measured using a Thermo Scientific™ FH‐40G survey meter. Experiments involved a water tank phantom (60 × 30 × 30 cm 3 ) representing the patient that was uniformly irradiated using a 3 mm spot diameter proton pencil beam with 10 cm modulation width, 19.95 cm distal beam range, and 10 × 10 cm 2 field size. Results: Neutron spectrometry around the target volume showed two main components at the thermal and fast energy ranges. The study also revealed the large dependence of the energy distribution of neutrons, and consequently of out‐of‐field doses, on the primary beam direction (directional emission of intranuclear cascade neutrons) and energy (spectral composition of secondary neutrons). In addition, neutron mapping within the facility was conducted and showed the highest H ∗ (10) value of ∼51 μ Sv Gy −1 ; this was measured at 1.15 m along the beam axis. H ∗ (10) values significantly decreased with distance and angular position with respect to beam axis falling below 2 nSv Gy −1 at the entrance of the maze, at the door outside the room and below detection limit in the gantry control room, and at an adjacent room (<0.1 nSv Gy −1 ). Finally, the agreement on H ∗ (10) values between all detectors showed a direct dependence on neutron spectra at the measurement position. While conventional rem‐counters (LB 6411, RadEye™ NL, NM2‐458) underestimated the H ∗ (10) by up to a factor of 4, Hawk TEPCs and the WENDI‐II range‐extended detector were found to have good performance (within 20%) even at the highest neutron fluence and energy range. Meanwhile, secondary photon dose equivalents were found to be up to five times lower than neutrons; remaining nonetheless of concern to the patient. Conclusions: Extended‐range BSS, TEPCs, and the WENDI‐II enable accurate measurements of stray neutrons while other rem‐counters are not appropriate considering the high‐energy range of neutrons involved in proton therapy.